The Impact of a Brief Teaching English towards the Drivers Online Transportation in Dealing with ASIAN GAMES 2018 - Becce Tenridinanti , Tamara; Susanti, Rini; Indawan, (International Journal of Psychosocial Rehabilitation, 2020)
The problem examined in this scientific paper was the impact of a brief teaching English for online transportation drivers in facing ASIAN GAMES 2018. This scientific paper was motivated by the problem of the lack of understanding of English that owned by online transportation drivers so that it would be difficult for them to communicate with foreigners. It aimed to determine the impact of a brief teaching English for online transportation drivers in facing ASIAN GAMES 2018. The method of scientific paper used was quantitative with a percentage analysis of the results of the questionnaire. Data collection techniques used were interview. In this case, Victory Sriwijaya Education has conducted short period teaching English with a quota of 50 Grab partners to prepare for ASIAN GAMES 2018. However, only 29 people participated in this study, 21 other people were unable to attend the Grab event on March 11, 2018 for several reasons. The result of scientific paper was after the existence of short teaching English, the impact of which felt by the drivers of online transportation quite well and they argued that they want to have teaching English continuously.